Refractive and Visual Outcomes of Pediatric Cataract Surgery in Indonesian Tertiary Eye Center - Memed, Feti Karfiati; Santosa, Rizki Adi; Irfani, Irawati; Caesarya, Sesy; Amiruddin, Primawita Oktarima; Kuntorini, Mayasari Wahyu (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2025)
Introduction: Cataract remains as a leading cause of visual impairment in children. Surgical intervention and post-operative refractive correction remain fundamental. This study aims to describe the refractive and visual outcome of pediatric cataract surgery in a tertiary eye center in Indonesia. Methods: This retrospective study was conducted utilizing medical records of all congenital and developmental cataracts patients undergoing cataract extraction procedures with or without primary IOL implantation between January and December 2022. Exclusion criteria included patients who did not undergo visual acuity and objective refraction examination 1-month post-cataract surgery and those with incomplete medical records data. Results: A total of 118 eyes from 65 patients was included in this study. Most patients had bilateral cataracts (93.80%) and operated at the median age of 18 (0.96-212.64) months. Post-operatively, there were 71 (60.19%) aphakic and 47 (39.81%) pseudophakic patients with a respective refractive status of +18.00 (12.00 – 21.13) D and +0.60 (±2.37) D. Prediction error (PE) and absolute prediction error (APE) were obtained within 1.00 D. Most aphakic patients had unquantifiable visual acuity both before (91.50%) and after (83%) surgery. Among pseudophakic patients, nine (19.16%) had visual acuity of ≥ 6/12 and seven (14.89%) had visual acuity of <6/12 - 6/18 post-operatively. No patients had visual acuity ≥ 6/12 and <6/12 - 6/18 before surgery. Conclusion: Post-operative refractive status of both aphakic and pseudophakic patients were well within correctable range. There was an improvement of vision after surgery. Limited visual potential may be attributed to the presence of amblyopia.